1976
DOI: 10.1172/jci108256
|View full text |Cite
|
Sign up to set email alerts
|

Hormone-sensitive fat cell adenylate cyclase in the rat. Influences of growth, cell size, and aging.

Abstract: A B S T R A C T The possibility has been explored that decreases of adenylate cyclase may explain diminished hormone sensitivity of adipose tissue with aging. Isolated cells were prepared from epididymal fat pads of rats 1-, 2-, 6-, 12-, and 24-mo-old, fixed in OsO, and sized and counted with a Coulter apparatus. Adenylate cyclase was assayed in cell membranes (ghosts) using [ra-P] 6 and 24 mo per cell. Glucagon stimulated adenylate cyclase 4.5-fold relative to basal in the 1-mo-old rat, but its effect then ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Viewed in this light, the adult animals show considerably less ability to adapt than do the young. Although stimulation by fluoride may not reflect total adenylate cyclase activity, fluoride stimulation and that with GMP-P (NH)P (plus high Mg2+) were closely parallel in our earlier report (2). The latter stimulus produces the highest adenylate cyclase activities seen to date.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Viewed in this light, the adult animals show considerably less ability to adapt than do the young. Although stimulation by fluoride may not reflect total adenylate cyclase activity, fluoride stimulation and that with GMP-P (NH)P (plus high Mg2+) were closely parallel in our earlier report (2). The latter stimulus produces the highest adenylate cyclase activities seen to date.…”
Section: Discussionsupporting
confidence: 77%
“…We have previously reported that no age-related decrease of epinephrine activation (stimulated/basal) is seen in animals fed ad lib. Absolute activity with epinephrine decreased between 2 and 6 mo but thereafter only slightly until after 12 mo; at 24 mo a modest decrease of epinephrine-and fluoride-stimulated activity was apparent, suggesting loss of adenylate cyclase catalytic units by that time (2). In the present studies both basal and fluoride-responsive enzyme (per milligram protein and per cell) were decreased in 15-mo restricted rats compared to control animals of the same age, suggesting that adenylate cyclase catalytic units might also be lost during dietary restriction in these animals.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the rat, the impairment has been thought to be caused by an increased phosphodiesterase activity (13,29,30) or a more pronounced antilipolytic effect of adenosine (31,32). Nevertheless, a postreceptor defect has also been proposed (33).…”
Section: Discussionmentioning
confidence: 99%
“…A decreased lipolytic response to beta adrenergic stimulation has been demonstrated in vitro in older rats (5)(6)(7)(8)(9). Although the mechanism responsible for this change is not clear, studies with fat cell membranes (10) and isolated adipocytes (1 1) suggest that a reduction in adenylate cyclase activity is involved.…”
Section: Introductionmentioning
confidence: 99%